Impact of the SARS-CoV-2 Pandemic on Psychiatric Pathology treated in Pediatric Emergencies. (Revista de Medicina Clinica, 2023)
Letter to the editor on "Impact of the SARS-CoV-2 Pandemic on Psychiatric Pathology Treated in Pediatric Emergencies" presented in Issue 7 number 1 of 2023 of the Journal of Clinical Medicine.
Keywords: COVID-19; autolysis; Psychiatry